Peran PKK Desa Musirlor Kabupaten Nganjuk Dalam Pemberdayaan Perempuan Perspektif Ekonomi Islam - Nandia Kholifah Setiama Utami; Said Abadi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: The Family Welfare Movement (PKK) in Musirlor Village functions as acommunity-based organization that actively contributes to women’s empowerment at the local level. This study aims to: (1) analyze the empowerment programs carried out by the PKK for women in Musirlor Village, Nganjuk; (2) identify the factors that influence the role of the PKK in enhancing women’s empowerment; and (3) examine the impact of PKK strategies on improving women’s economic welfare from an Islamic economic perspective. Research methods: This research is classified as field research using a descriptive qualitative method. Data were collected through interviews, observations, and documentation involving PKK cadres and female beneficiaries in Musirlor Village. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with the validity of findings ensured using triangulation techniques. Result: The findings of the study reveal that: (1) the PKK plays a dual role as facilitator and motivator in women’s empowerment; (2) supporting factors include member enthusiasm, entrepreneurial spirit, and cadre collaboration, while inhibiting factors consist of limited financial resources, lack of continuous training, and low awareness of women regarding their economic potential; and (3) PKK strategies positively contribute to both economic and spiritual well-being. Several members have achieved economic independence and demonstrated increased self-confidence, aligning with the principles of Islamic economics.